Book Review: Demystifying Grounded Theory Selection - Gary L. Evans (Grounded Theory Review: An International Journal)
How to select a research methodology? What is the difference between CGT and QDA? Does grounded theory work with case studies? Is grounded theory the right selection for a PhD dissertation? These questions and many more are the focus of Dr. Glaser's new book, which addresses the key issues faced by the novice researcher in selecting classic grounded theory as their research methodology. In this 439 page fifteen-chapter book, Dr. Glaser takes the research reader on a journey reviewing the history, issues, and factors to consider in selecting classic grounded theory and challenges and myths around what is and is not grounded theory.